A heuristic Approach of Wimax System with Different Modulation Process - Vaishnavi, M (International Journal of Computer Sciences and Engineering, 2025)
WiMAX has several competitors within the market, together with cellular 3G and LTE specifications. although every of those technologies has its own benefits and drawbacks, mobile WiMAX has a grip as a result of it's associate all IPbased packet switched network designed for information traffic WiMAX is that the finish to finish technology that has low price applications and walk resolution for broadband wireless access. WiMAX is predicated on the quality family outlined by IEEE 802.16 that provides Coverage of up to thirty miles (last mile) compared to alternative technologies. WiMAX has distinctive characteristics that permits the bottom station to handle thousands of subscriber stations (SS), it conjointly provides economical relinquishing procedure and Power management mechanism by introducing the sleeping mode for mobile stations. The key downside of WIMAX system is high BER and as BER will increase, signal to noise quantitative relation decreases. It means, the less the BER, result's the upper the SNR and also the higher communication quality This paper presents simulation of WiMAX exploitation OFDM technique exploitation secret writing technique . BER versus Eb/No curves area unit used for comparison the results